Persuasion Action Strategies in Da'wah Discourse on Social Media in the Global Communication Era - Kusmanto, Hari; Prayitno, Harun Joko; Sofiana, Isnaeni; Jamaluddin, Norliza (Language Circle: Journal of Language and Literature, 2021)
Creative and suggest speech partners. This study aimed to identify the persuasion action strategies in da'wah discourse on social media of Instagram. The approach of this study was descriptive qualitative. The data of this study was persuasion utterances in da'wah discourse on social media. The data collection employed documentation, transcription, and listening method and was followed by note-taking techniques. The data analysis of this study used the distributional method and markup reading technique. The results of this study showed that there are eleven persuasion strategies used by Ustadz Hanan Attaki in da'wah through social media of Instagram. The eleven strategies include (1) the use of Al-Qur'an, (2) directly persuasion (3) indirectly persuasion, (4) persuasion using repetition, (5) the use of stories, (6) the use of the figure of speech, (7) the use of hope, (8) ) the use of analogy, (9) the use of Al-Hadith, (10) the use of expressiveness, and (11) the use of cause and effect. In the era of global communication, the realization of da'wah on social media can utilize persuasive language to influence speech partners so that the purpose of da'wah can be successful